Gender inequity in the medical profession: the women doctors in Spain (WOMEDS) study - Claudia Santucci; Beatriz González López-Valcarcel; Cristina Avendaño-Solá; Mari Carmen Bautista; Carmen Gallardo Pino; Lourdes Lledó García; Elena Martín-Perez; Pilar Garrido López (BMC, 2023)
Abstract Background The long-standing underrepresentation of women in leadership positions in medicine is well-known, but poorly documented globally. There is some evidence of the gender gap in academia, medical society leadership, or specific problems in some specialties. However, there are no investigations analyzing all medical specialties together and reporting the glass ceiling from a 360º perspective that includes positions in academia, research, professional organizations, and clinical activity. Additionally, the majority of studies have a US perspective, and we wonder if the perspective of a European country might be different. The WOmen in MEDicine in Spain (WOMEDS) project ( https://womeds.es ) aims to describe and characterize, in a systematic and detailed way, the gender bias in the medical profession in Spain in order to monitor its evolution over time and contribute to prioritizing gender policies. Methods We retrieved data for the calendar years 2019-2021 from several sources and selected surveys. We built four groups of indicators to describe leadership positions in the medical profession: (i) leadership in healthcare according to specialty and region; (ii) leadership in scientific and professional bodies; (iii) academic career; and (iv) leadership in clinical research activity. As a summary measure, we reported the women ratios, calculated as the percentage of women in specific top positions divided by the percentage of women in the relevant population. Results We found gender inequity in leadership positions in all four settings. During the observed period, only 27.6% of the heads of departments in hospitals were women compared to 61.1% of women in medical staff. Ten of the 46 medical societies grouped in the Spanish Federation of Medical Societies (FACME) (21.7%) had a women president at some point during the study period, and only 4 annual congresses had ratios of women speakers higher than 1. Women were over-represented in the lower positions and underrepresented in the top academic ones. Only 26% and 27%, respectively, of the heads of departments and deans were women. The applications for public funding for research projects are led by women only in 45% of the cases, and the budget granted to women in public calls was 24.3% lower than that of men. Conclusion In all the areas analyzed, the leadership positions are still mostly occupied by men despite the feminization of medicine in Spain. The severe gender inequity found calls for urgent interventions within a defined time horizon. Such measures must concern all levels, from national or regional regulation to changes in organizational culture or incentives in specific organizations.